Effects of arsenite stress on growth and proteome of Klebsiella pneumoniae - Daware, Vandana; Kesavan, Suresh K.; Patil, Rajendra; Natu, Arvind; Kumar, Ameeta; Kulkarni, Mahesh J.; Gade, Wasudeo N. (Journal of Biotechnology, 2012)
In the present study an arsenite, As(III), tolerating bacterium, MR4, was isolated from Mulla River Pune, India, capable of reducing arsenate to arsenite and identified as Klebsiella pneumoniae (HQ857583). Comparative proteomic analysis using two-dimensional gel electrophoresis (2-DGE) and matrix assisted laser desorption ionization-time of flight-time of flight (MALDI-TOF/ TOF) was used to monitor the proteins undergoing changes in expression levels under 2.5 mM As(III) stress. The 2-DGE proteome map has shown that 60 proteins were differentially expressed under As(III) stress, of which 39 proteins were successfully identified with a MASCOT score greater than 70 (p < 0.05). Among the identified proteins, membrane transport/ binding proteins, porins, and amino acid metabolism enzymes were down-regulated while stress responsive proteins and antioxidant enzymes were up-regulated. Proteins involved in carbohydrate metabolism, particularly those in pentose phosphate pathway were also up-regulated while those involved in pyruvate metabolism were down-regulated. However, proteins involved in glycolysis and tricarboxylic acid cycle showed a mixed regulation response. These findings provide new insights into the probable mechanisms by which K. pneumoniae (HQ857583) could be adapting to As(III) stress. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: (2-DGE); Arsenite stress; Klebsiella pneumoniae; MALDI-TOF-TOF; Two dimensional gel electrophoresis

Zoom-in - a targeted database search for identification of glycation modifications analyzed by untargeted tandem mass spectrometry - Bhonsle, Hemangi S.; Korwar, Arvind M.; Kesavan, Suresh K.; Bhosale, Santosh D.; Bansode, Sneha B.; Kulkarni, Mahesh J. (European Journal of Mass Spectrometry, 2012)
Post-translational modifications (PTMs) are very important to biological function, however their identification and characterization is technically challenging. In this study, we have identified glycation modifications by nano LC-MSE, a data independent acquisition work flow, followed by database search using the Protein Lynx Global Server (PLGS). PLGS search with a complete human protein database hardly identified glycation modifications in a glycated human serum albumin (HSA), which was detected to be glycated by western blotting with advanced glycation end products (AGE) antibody and fluorescence spectroscopy. To overcome this difficulty, ``Zoom-In'' approach, a targeted database search was used to identify glycation modifications in a glycated HSA, which were further manually validated. This approach was useful for identification of glycation modifications from untargeted tandem mass spectrometry workflow such as MSE, but may require the development of a new algorithm or an upgrade of the existing software.
Keywords: advanced glycation end products (AGEs); data independent acquisition; Diabetes; post-translational modifications

Proteome wide reduction in AGE modification in streptozotocin induced diabetic mice by hydralazine mediated transglycation - Kesavan, Suresh K.; Bhat, Shweta; Golegaonkar, Sandeep B.; Jagadeeshaprasad, Mashanipalya G.; Deshmukh, Arati B.; Patil, Harshal S.; Bhosale, Santosh D.; Shaikh, Mahemud L.; Thulasiram, Hirekodathakallu V.; Boppana, Ramanamurthy; Kulkarni, Mahesh J. (Scientific Reports, 2013)
The non-enzymatic reaction between glucose and protein can be chemically reversed by transglycation. Here we report the transglycation activity of hydralazine using a newly developed MALDI-TOF-MS based assay. Hydralazine mediated transglycation of HbA1c, plasma proteins and kidney proteins was demonstrated in streptozotocin (STZ) induced diabetic mice, as evidenced by decrease in protein glycation, as well as presence of hydralazine-glucose conjugate in urine of diabetic mice treated with hydralazine. Hydralazine down regulated the expression of Receptor for Advanced Glycation End products (RAGE), NADPH oxidase (NOX), and super oxide dismutase (SOD). These findings will provide a new dimension for developing intervention strategies for the treatment of glycation associated diseases such as diabetes complications, atherosclerosis, and aging.

Molecules with O-acetyl group protect protein glycation by acetylating lysine residues - Vannuruswamy, Garikapati; Jagadeeshaprasad, Mashanipalya G.; Kashinath, K.; Kesavan, Suresh K.; Bhat, Shweta; Korwar, Arvind M.; Chougale, Ashok D.; Boppana, Ramanamurthy; Reddy, D. Srinivasa; Kulkarni, Mahesh J. (RSC Advances, 2016)
Pharmaceutical intervention for reduction of advanced glycation end products (AGEs) is considered as a therapeutic strategy to attenuate the pathogenesis of diabetes. Many molecules have been reported to possess antiglycation activity, one such example is acetylsalicylic acid (aspirin). It protects proteins from glycation by acetylating the lysine residues. Therefore, in this study we have synthesized and screened molecules containing free N-acetyl, O-acetyl and acetophenone groups. All the selected molecules in this study showed glycation inhibition but interestingly, only molecules with O-acetyl but not N-acetyl and acetophenone groups were capable of acetylating lysine residue. Furthermore, we have demonstrated that pre-acetylation or aspirin treatment prior to the induction of diabetes helps in reducing HbA1c and AGE formation in the streptozotocin induced diabetic mice. Hence pre-acetylation may have an additional therapeutic efficacy of reducing AGE levels in vivo. Incorporation of O-acetyl group into anti-diabetic molecules could be a useful strategy, as it may have an additive effect in reducing AGEs. Identification of such novel acetylating agents represents a new area in the drug discovery process.